A Importância do Planejamento Urbano Ambiental A Habitação Social e a Expansão Urbana em Presidente Prudente - Albano, Mayara Pissutti (2013)
The constant urbanization process in Brazil generates cities wanting infrastructure, dignified housing and public services, showing serious social and spacial segragation. The lack of public policies for housing and execution of adequate housing complexes create cities with illegal areas and uncontrolled expansion. At the same time, the neglect towards environmental legislation when planning social housing is bringing forth problems to its residents, as well as for the natural environment; in other words, the approval and implantation of complexes without the proper environmental analysis reinforces inadequate spaces and/or strongly impactful in the natural and built environments, reinforcing situations of segregation and degradation of the environment. In Presidente Prudente, many housing enterprises of social interest were implanted without adequate study or concern with the local environmental questions, as well as with legislation of land subdivision. Regarding this issues, this reasearch aims to contribute to a critical analysis about the production of social housing, verifying characteristics of implantation of social housing enterprises, its localization in the urban structure, the natural environment whre it was executed, the legal questions for approval in the competent agency of environmental licensing, among other relevant aspects. The object of study of this dissertation is focused in the Residencial Maré Mansa, executed in the city of Presidente Prudente by the private sector, in 1998. The methodology that is proposed to be followed is based in theoretical deepening on the mentioned aspects, research on the process of urban evolution of Presidente Prudente s design, legal aspects on social housing and environmental analysis, evidence base of approval in the competent agencies, social, environmental and physical characterization of the enterprise that was studied, and field research. It is aimed, then, to verify in a solid way the characteristics of the analyzed housing complex proving the lack of environmental control in the execution oof social house in the city.